HEGEMONI GURU TERHADAP MURID DALAM NOVEL â€œSANG PENDIDIKâ€ KARYA AGUK IRAWAN MN (KAJIAN SOSIOLOGI SASTRA): Bahasa Indonesia - alfaza, alfaza safira (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research uses the object of the novel "The Educator" by Aguk Irawan MN. This novel tells the hegemony of intellectual figures and social classes who influence by instilling their ideology in certain groups by inviting goodness. The purpose of this research is to find and describe the hegemony of teachers to students in the novel "The Educator" by Aguk Irawan MN. In this study using qualitative methods by collecting data library and document techniques. The data source in this study was obtained from the novel "The Educator" by Aguk Irawan MN, published by Qalam Nusantara. Data analysis techniques in this study used a hermeniotic reader analysis technique, namely the stages of reading, marking, coding, interpretation and presentation of conclusions. The results of this study discuss the hegemony of Martokan as a teacher to his students. Martokan hegemony his students by giving advice to be a good person, Martokan also hegemony through the material described to tell the history of Sunan Drajat and Sunan Duwur, so that it will make his students enthusiastic in learning the Koran.